Dietary diversity among preschoolers: A cross-sectional study in poor, rural, and ethnic minority areas of Central South China - Bi, Jieying; Liu, Chengfang; Li, Shaoping; He, Zhenya; Chen, Kevin Z.; Luo, Renfu; Wang, Zimeiyi; Yu, Yanying; Xu, Haiquan (MDPI, 2019)
The aim of this study was to document the dietary diversity status of preschool children in poor, rural, and ethnic minority areas of Central South China and examine its associated factors both at home and in preschools. A cross-sectional study including 1328 preschool children aged three or five years from two nationally designated poverty counties in Hunan Province was conducted. A dietary diversity score (DDS) was constructed to measure the dietary patterns based on the 24 h recall method. The mean DDS among the sample children was 5.77 (95% confidence interval: 5.70–5.83, range 1 to 9) with a standard deviation of 1.22. Both household characteristics (including the education level of the child’s primary caregiver and the nutritional knowledge of the caregiver) and preschool factors (including the nutritional knowledge of the child’s preschool principal and teachers, nutritional training to children, and the preschool kitchen manager) were positively associated with children’s DDS. The dietary diversity status of children in poor, rural, and ethnic minority areas of Central South China is much lower than that of their peers in other areas. Nutritional education should be provided to caregivers, preschool staff, and children to narrow the gap